Constitutional Principle, the Rule of Law and Political Reality: The European Union (Withdrawal) Act 2018. Issue 2 (5th March 2019) - Craig, Paul
Abstract: The European Union (Withdrawal) Act 2018 is the cornerstone of UK legislation designed to accomplish the legal dimension of Brexit. It brings the entire acquis of EU law into UK law in order to avoid regulatory black holes that would otherwise occur. The Act embodies a twofold legislative strategy: EU law brought into UK law thereby is to be made fit for purpose by exit day, with necessary changes being made by statutory instrument; Parliament can then decide at greater leisure thereafter whether it wishes to retain, amend or repeal this legislation. The burden placed on Parliament is unprecedented, all the more so given the exigencies of time in which the changes are to be made. This article explicates the principal provisions of the 2018 Act, and the concerns as to constitutional principle and the rule of law raised by the legislation. The tensions in the drafting process are made apparent, and uncertainties in the resulting text are revealed.